Omentoplasty for ventricular assist device infections: Encouraging outcomes - Ahmed M. El Banayosy, MD; Susan George, DNP, APRN; David W. Vanhooser, MD; Hendra Setiadi, PhD; Daniel R. Freno, MD; Marshall T. Bell, MD; Craig C. Elkins, MD; Mircea R. Mihu, MD; Douglas A. Horstmanshof, MD; Aly El Banayosy, MD; James W. Long, MD, PhD (JHLT Open)
Background: LVAD infections are associated with substantial morbidity and mortality. We explored the impact of surgical Omentoplasty (OMP) added to Incision and Debridement (I&D) plus Antibiotic therapy (AB) on survival and infection-related readmissions in patients with LVAD infections. Methods: Thirty-three patients with deep LVAD-specific infections were studied over a period of 12 years. Survival and readmissions for recurrent infection in subjects receiving I&D and ABs alone (Group A, n = 15) were compared to those in whom OMP was added to I&D and ABs (Group B, n = 18). Results: Baseline characteristics were similar between groups, as well as infectious organisms. Two-year survival was significantly improved in Group B (OMP + I&D + ABs) as compared to Group A (I&D + ABs without OMP) [77% vs. 7%; p < 0.001]. Recurrent infection-related readmissions were notably lower in Group B compared to Group A (0.18 vs. 0.24 admissions/patient-year), with a significant reduction within Group B following the application of OMP (0.13 to 0.06 admissions/patient-year). Following OMP, intravenous (IV) antibiotics were successfully replaced with oral long-term ABs in the 78% of patients. No long-term antibiotic-related complications were noted. Conclusion: This report, comprising the most extensive such experience to date, indicates that combining surgical Omentoplasty (OMP) with incision and debridement (I&D) plus antibiotic (AB) treatment is remarkably effective for suppressing deep LVAD infections, improving survival and decreasing infection-related readmissions. Filling the open space around an implanted LVAD with highly vascularized omentum, as a living tissue with anti-infective properties, appears to be effective for improving outcomes with LVAD infections.